A Carbon Footprint of Medical Faculties in B J Medical College, Ahmedabad City, Gujarat, India - Vyas, Monark; Bhatt, Rajashree (National Journal of Community Medicine, 2018)
Introduction: A Carbon footprint measures human consumption of natural resources in comparison to Earth's ecological capacity to regenerate them. It represents the human impact on the Earth in a clear manner. Material & methods: This cross-sectional study was carried out among faculty members of B.J Medical College & Hospital Ah- medabad, Gujarat, India. The study was conducted in month of June to October 2011. Study Participants included 125 medical doctors of different departments of the college and hospital inter- viewed by pre-designed and a pre-tested questionnaire. Coded data were analyzed in Epi info version 3.5.1. Percentages have been presented. Results: Male: female ratio 56:44.Their carbon foot-print was poor because 88% of them didn’t use share-based vehicles or public transport. Only 5.6% had solar devices at home. Housing-footprint was good as 100% of them used water-saving-techniques at home. Use of elevator (40.6%) was found common. 62.4% never used or- ganic food. Goods & service foot-print was poor; only 13.6% didn’t use plastic bags on daily basis. 23.2% never bothered about usage of mobile phones, 12.8% were not interested in tree- plantation.